Digital Image Security with AES and Blowfish Double Encryption - Asep Id Hadiana; Melina; Iqbal Dwi Nulhakim (Research Collaboration Community (RCC), 2025)
Protection of digital images is becoming increasingly important with the growing use of images as a medium of information in various fields, particularly in the healthcare sector. Medical images such as Magnetic Resonance Imaging (MRI) contain sensitive information that requires extra security against unauthorized access and data manipulation. This study aims to design and build a digital image security system using a dual encryption approach and authenticity verification based on watermarking. The security process is carried out in two main stages. First, images with text-based watermarks are encrypted using the Advanced Encryption Standard (AES) algorithm to protect their visual content. Second, the AES key is re-encrypted using the Blowfish algorithm to prevent the key from being stored in plaintext, thereby creating an additional layer of protection. The watermark is embedded into the image using the Singular Value Decomposition (SVD) method and is first converted into a hash value using the SHA-256 algorithm, which serves to verify the integrity of the image after decryption. The testing was conducted using the public dataset “Brain Tumor Image Dataset (Semantic Segmentation)” from Kaggle, which consists of brain MRI images in .jpg and .png formats. The system evaluation encompassed functionality, data security, and process efficiency through system function testing, measurement of encrypted data randomness (entropy test), file penetration using OpenSSL, and performance analysis in terms of processing time and file size. The research results show that the system successfully implemented double encryption with a high entropy level (approaching 8.00) and resistance to penetration attacks. In terms of efficiency, the system achieved an average encryption time of 81.35 ms and decryption time of 13.68 ms with minimal file size increase. Integrity testing confirmed that the SVD-SHA256-based watermark remained intact after the encryption-decryption process, enabling verification of image authenticity. The developed system efficiently maintains the confidentiality and authenticity of digital images and can be applied in electronic medical record systems or sensitive digital archives. Keywords: Digital images, double encryption, AES, Blowfish, SVD